Genetic Characterization of Three Deer Species in Malaysia - A. El-Jaafari, Habiba Ali (2005)
In recent years, there has been much interest in the domestication and farming of deer in Malaysia for velvet, skin and meat production. Various deer species and subspecies have been imported into the country and this has resulted in the introduction of new germplasm and the risk of mixture of these, making it necessary to evaluate the genetic background of the various species before they are indiscriminately diluted or altered. This study was carried out to characterize three deer species i n Malaysia, namely rusa (Cervus timorensis), sambar (Cervus unicolor) and sika (Cervus nippon), by using the karyotyping, biochemical polymorphisms and randomly amplified polymorphic DNA (RAPD) techniques. The rusa herd at the Deer Breeding Unit of University Research Park, Universiti Putra Malaysia, the sambar herd at Pusat Permbiakan Ternakan Sabray, Kenungu, Sabah and the sika herd at Pusat Temakan Haiwan, Batu Arang were used as the research populations. Conventional, G-banded and C-banded karyotypes were generated for three male and three female deer of each species. The chromosome number was derived from 100 good metaphase spreads per animal. The morphology of the chromosomes was based on their relative lengths and position of the centromeres. Rusa, sambar and sika displayed a total of 60, 62 and 66 chromosomes in the majority of the cell spreads, respectively. The rusa deer had five pairs of metacentric/submetacentric and 24 pairs of acrocentric autosomes, and a pair of sex chromosomes. The X chromosome was characterised as the largest acrocentric chromosome, while the Y chromosome was a small acrocentric chromosome. The sambar deer had four pairs of metacentric/submetacentric and 26 pairs of acrocentric autosomes. The sex chromosomes were similar to that of rusa deer. In the sika deer there were two pairs of metacentric/submetacentric and 30 pairs of acrocentric autosomes. The pair of sex chromosomes was similar to those of the rusa and the sambar. The homologous chromosomes were paired with respect to their sizes, shapes and banding patterns generated from C-banding and G-banding. The nucleolar organizer regions (NORs) for the three deer species were 1 ocated on different chromosomes. The male r usa displayed NORs on the telomeric regions both homologues of Chromosomes 1 and 6, but the female displayed NORs on only one homologue of Chromosome 1, and both homologues of Chromosome 6. Male and female sambar deer both had three telomeric NORs located on the homologous pair of Chromosome 6 and a single homologue of Chromosome 7. Female and male sika deer displayed four NORs which were on the acrocentric Chromosomes 1 and 2. Cellulose acetate and starch g el electrophoresis were u sed to s tudy e nzymelprotein polymorphisms. Blood samples from 38 rusa, 9 sambar and 34 sika deer were analysed for 15 b iochemical m arkers, h owever, only six m arkers generated results. Lactate dehydrogenase (LDH), Albumin (ALB), Transferrin and X-protein were monomorphic. Haemoglobin (HB) was polymorphic with three phenotypes for the three species, which could b e attributed to two c odominant alleles, H B~ and HB*. The frequency of H B w~as highest in the rusa population, 0.553, while HBB was predominant in sambar, 0.61 1, and sika, 0.574. The rusa and sika populations showed significant (P<0.05) deviations from HWE for this locus. Glucose-6-phosphate dehydrogenase (GGPD), although polymorphic, was monomorphic within each species. Rusa and sambar showed the same phenotype, but this was different from that of the sika. The genetic distance between rusa and sambar based on the above biochemical markers was 0.001, between rusa and sika it was 0.144, and between sambar and sika it was 0.141. The animals used in the biochemical study were a Iso analyzed for RAPD markers using 10 arbitrary primers. The primers amplified a total of 164 makers, of which 59 were shared by a 11 three species. The overall percent polymorphism was 9 9.39%, with rusa showing 128 polymorphic markers (97.71%), sambar showing 66 (68.04%) and sika showing 118 (95.16%) polymorphic markers. The 62B-1 (800 bp) band was a c ornrnon monomorphic m arker for the three species. Sambar had five e xclusive monomorphic markers, while sika had one and rusa none. The genetic distance based on Dice and Jaccard similarity indices showed sambar and sika to be the most closely related, followed by rusa and sambar.